Cognitive Performances: The Role of Digit Ratio (D2:D4) With a Protective Factor for Anxiety - Rinella, Sergio; Massimino, Simona; Sorbello, Alessia; Perciavalle, Vincenzo; Coco, Marinella (Frontiers in Neuroergonomics, 2022)
This study aimed to identify a possible correlation between the D2:D4 ratio and state and/or trait anxiety in adult healthy subjects and, if so, whether it exists any difference between men and women. In addition, we also wanted to observe whether there is a relationship between participants' age and state and/or trait anxiety. The research involved 125 subjects of both sexes, who were calculated the D2:D4 ratio and were administered the self-assessment questionnaire State-Trait Anxiety Inventory (STAI-Y). Results show that there are positive significant correlations between the D2:D4 ratio and score at state anxiety and trait anxiety, in the total sample. However, if men are examined separately from women, it can be observed that only men have a statistically significant relationship between D2:D4 ratios and state anxiety and trait anxiety. Moreover, about possible relations between the age of participants and state and trait anxiety, a significant negative relationship was observed, without differences between men and women. However, only subjects with a D2:D4 ratio ≥ 1, without differences between men and women, showed a statistically significant negative linear correlation between their age and their state and trait anxiety. The present data allow us to conclude that a low D2:D4 ratio (<1) represents a protective factor against anxiety in both men and women and that this protection seems likely to act throughout life.